To find the equation of the line after translating it, we start with the original line equation:
\[ y = 3x + 2 \]
Step 1: Shift the line 1 unit to the right.
When we shift a line to the right by \(h\) units, we replace \(x\) with \(x - h\) in the equation.
For a shift of 1 unit to the right:
\[ y = 3(x - 1) + 2 \]
\[ y = 3x - 3 + 2 \]
\[ y = 3x - 1 \]
Step 2: Shift the line 2 units up.
When we shift a line up by \(k\) units, we add \(k\) to the entire equation.
For a shift of 2 units up:
\[ y = 3x - 1 + 2 \]
\[ y = 3x + 1 \]
Thus, the equation of the new line after translating 1 unit to the right and 2 units up is:
\[ y = 3x + 1 \]
Among the provided options, the correct choice is:
\(y = 3x + 1\).